2023
DOI: 10.4251/wjgo.v15.i8.1475
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen, carbohydrate antigen 199 and carbohydrate antigen 724 in gastric cancer and their relationship with clinical prognosis

Abstract: Colitis-associated colorectal cancer (CAC) is defined as a specific cluster of colorectal cancers that develop as a result of prolonged colitis in patients with inflammatory bowel disease (IBD). Patients with IBD, including ulcerative colitis and Crohn’s disease, are known to have an increased risk of developing CAC. Although the incidence of CAC has significantly decreased over the past few decades, individuals with CAC have increased mortality compared to individuals with sporadic colorectal cancer, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Herein, our study showed that NLR and PLR had a strong correlation with LVI. At present, several tumor markers, such as CEA, CA19-9 and CA724 have been widely used in the diagnosis, prognosis evaluation, and efficacy testing of patients with GC [ 23 , 24 ]. Moreover, CA724 had the highest diagnostic efficiency and it is associated with tumor biological behavior such as tumor size, depth of invasion, stage and lymph node involvement [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, our study showed that NLR and PLR had a strong correlation with LVI. At present, several tumor markers, such as CEA, CA19-9 and CA724 have been widely used in the diagnosis, prognosis evaluation, and efficacy testing of patients with GC [ 23 , 24 ]. Moreover, CA724 had the highest diagnostic efficiency and it is associated with tumor biological behavior such as tumor size, depth of invasion, stage and lymph node involvement [ 25 ].…”
Section: Discussionmentioning
confidence: 99%